Difference between revisions of "Forest UCM Osc Driven"

From New IAC Wiki
Jump to navigation Jump to search
 
(21 intermediate revisions by the same user not shown)
Line 36: Line 36:
 
:<math>  D x  = f(t)</math>
 
:<math>  D x  = f(t)</math>
  
;Linear differential equations have coefficient that can constant or variable coefficients that can be transformed into constant coefficients.
+
;Linear differential equations have coefficients that can be constant or variable coefficients that can be transformed into constant coefficients.
  
  
Line 49: Line 49:
  
 
:<math>D(ax) = aD(x)</math> and <math>D(x_1 + x_2) = D(x_1) + D(x_2)</math>
 
:<math>D(ax) = aD(x)</math> and <math>D(x_1 + x_2) = D(x_1) + D(x_2)</math>
 
  
 
==Solving the Inhomogeneous Diff. Eq. ==
 
==Solving the Inhomogeneous Diff. Eq. ==
Line 58: Line 57:
  
  
Since the solution of the 2nd order differential equation requires exactly two arbitrary constant,
+
Since the solution of the 2nd order differential equation requires exactly two arbitrary constants,
  
 
We can formulate the solution by tacking a particular solution onto the homogeneous solution that already has two arbitrary constants.
 
We can formulate the solution by tacking a particular solution onto the homogeneous solution that already has two arbitrary constants.
Line 103: Line 102:
 
;Trick: If a differential equation has the cosine function as a solution then the sine function may also be a solution since the difference between the two is only a phase shift.
 
;Trick: If a differential equation has the cosine function as a solution then the sine function may also be a solution since the difference between the two is only a phase shift.
  
It must also be try that  
+
It must also be true that  
  
 
:<math>D(y_p) = f_0 \sin ( \omega t)</math>
 
:<math>D(y_p) = f_0 \sin ( \omega t)</math>
Line 115: Line 114:
 
the constant C is determine by substituting the solution into the equation  
 
the constant C is determine by substituting the solution into the equation  
  
:<math>D(z_p) = \left ( - \omega^2 + 2 i \beta \omega + \omega_0 \right )  C e^{i \omega t}  = f_0 e^{i \omega t}</math>  
+
:<math>D(z_p) = \left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  C e^{i \omega t}  = f_0 e^{i \omega t}</math>  
  
::<math>\Rightarrow C= \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0 \right )  } </math>
+
::<math>\Rightarrow C= \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  } </math>
  
 
The amplitude of the solution is a complex number that may be cast in terms of a real amplitude times the complex exponential such that  
 
The amplitude of the solution is a complex number that may be cast in terms of a real amplitude times the complex exponential such that  
Line 125: Line 124:
 
where the real amplitude A is given by  
 
where the real amplitude A is given by  
  
:<math>A^2 = C C* = \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0 \right )  } \left ( \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0 \right )  }\right )^*</math>
+
:<math>A^2 = C C* = \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  } \left ( \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  }\right )^*</math>
:: <math>= \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0 \right )  } \left ( \frac{f_0} {\left ( - \omega^2 - 2 i \beta \omega + \omega_0 \right )  }\right )</math>
+
:: <math>= \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  } \left ( \frac{f_0} {\left ( - \omega^2 - 2 i \beta \omega + \omega_0^2 \right )  }\right )</math>
:: <math>= \frac{f_0^2} { (\omega^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }</math>
+
:: <math>= \frac{f_0^2} { (\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }</math>
 +
 
 +
:<math> C = A e^{-i\delta}= \sqrt{\frac{f_0^2} { (\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }} e^{-i\delta}</math>
 +
 
 +
:<math>z_p = C e^{i \omega t}=\sqrt{\frac{f_0^2} { (\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }} e^{-i\delta} e^{i \omega t}= C e^{i \omega t}=\frac{f_0} { \sqrt{(\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }}e^{i (\omega t-\delta)}</math>
 +
 
 +
 
 +
==== What is delta?====
 +
:<math> C =  \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  } = A e^{-i\delta} </math>
 +
:<math>  \frac{f_0} {\left ( - \omega^2 + 2 i \beta \omega + \omega_0^2 \right )  } = A e^{-i\delta} </math>
 +
:<math>  {f_0} e^{i\delta} = A \left ( (\omega_0^2- \omega^2) + 2 i \beta \omega  \right )  </math>
 +
 
 +
Since <math>f_0</math> and <math>A</math> are not imaginary variables
  
:<math> C = A e^{-i\delta}= \sqrt{\frac{f_0^2} { (\omega^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }} e^{-i\delta}</math>
+
The phase (<math>\delta</math>) must be due to the remaining complex term <math> \left ( (\omega_0^2- \omega^2) + 2 i \beta \omega  \right )</math>
 +
 
 +
To determine the angle <math>\delta</math> we construct a right triangle in the complex plane where the leg along the real axis is given by <math>(\omega_0^2- \omega^2)</math>  and the other leg of the triangle is along the imaginary axis with a length of <math> 2 \beta \omega</math>
 +
 
 +
:<math>\tan \delta = \frac{2 \beta \omega}{(\omega_0^2- \omega^2)}</math>
 +
:<math>\delta = \tan^{-1}\left ( \frac{2 \beta \omega}{(\omega_0^2- \omega^2)} \right )</math>
 +
 
 +
;The final complex solution si :
 +
 
 +
:<math>z_p =\frac{f_0} { \sqrt{(\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }}e^{i (\omega t-\delta)}</math>
 +
 
 +
 
 +
with
 +
 
 +
:<math>x_p = \mbox{Real} \left |z_p \right | = \frac{f_0} { \sqrt{(\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }} \cos(\omega t-\delta)</math>
 +
 
 +
==Complete Solution for the Driven Damped oscilaltor==
 +
 
 +
:<math>x(t) =x_h + x_p = C_1 e^{r_1 t} + C_2 e^{r_2 t} + A \cos(\omega t-\delta)</math>
 +
 
 +
where
 +
 
 +
:<math>r_1 = - \beta + \sqrt{\beta^2 - \omega_0^2}</math>
 +
:<math>r_2 = - \beta + \sqrt{\beta^2 + \omega_0^2}</math>
 +
:<math>A=\frac{f_0} { \sqrt{(\omega_0^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }}</math>
 +
:<math>\delta = \tan^{-1}\left ( \frac{2 \beta \omega}{(\omega_0^2- \omega^2)} \right )</math>
  
:<math>z_p = C e^{i \omega t}=\sqrt{\frac{f_0^2} { (\omega^2 - \omega^2)^2 + 4  \beta^2 \omega^2  }} e^{-i\delta} e^{i \omega t}</math>
 
  
  
 
[[Forest_UCM_Osc#Damped_Oscillations_with_driving_source]]
 
[[Forest_UCM_Osc#Damped_Oscillations_with_driving_source]]

Latest revision as of 23:23, 14 October 2021

Damped Oscillators driven by an external source

An external force must be supplied to do work on a damped oscillator in an amount that is equal to or greater than the work done by the dissipative force.


An external force (source) is added to the homogeneous differential equation making it inhomogenous

¨x+2β˙x+ω20x=0


making it

¨x+2β˙x+ω20x=f(t)

where f(t) represents the external force (source) that depends on time divided by the objects mass.


Differential equations in Operator form

In the previous sections we used the definition

O=ddt

to solve the second order linear differential equation.

Let's take this a step further with the following operator definition

D=d2dt2+2βddt+ω20

then

¨x+2β˙x+ω20x=f(t)

becomes

Dx=f(t)
Linear differential equations have coefficients that can be constant or variable coefficients that can be transformed into constant coefficients.


Note
D is a linear operator

meaning

D(ax1+bx2)=D(ax1)+D(bx2)

the above is a property of differential calculus where

D(ax)=aD(x) and D(x1+x2)=D(x1)+D(x2)

Solving the Inhomogeneous Diff. Eq.

To solve the Inhomogeneous problem we take advantage of the linear operator such that

D(xh+xp)=D(xh)+D(xp)=0+f=f


Since the solution of the 2nd order differential equation requires exactly two arbitrary constants,

We can formulate the solution by tacking a particular solution onto the homogeneous solution that already has two arbitrary constants.

All we need to do is find the particular solution xp that satisfies

D(xp)=f

and we will have a complete set of solutions.

Break the equation up into a Homogeneous solution and a Particular Solution


Homogeneous Solution

Th Homogenous solution solved the equation

Dxh=0

we know from the previous section that the homogenous solution has the form

xh=C1er1t+C2er2t

where

r1=β+β2ω20
r2=β+β2+ω20


Case 1 : f(t) is sinusoidal

Consider the case where the driving force is a sinusoidal function

f(t)=f0cos(ωt)

We seek a solution to the particular equation

D(xp)=f0cos(ωt)
Remember
ω is not necessarily at the natural (resonant) frequency ω0


Trick
If a differential equation has the cosine function as a solution then the sine function may also be a solution since the difference between the two is only a phase shift.

It must also be true that

D(yp)=f0sin(ωt)


You can construct a complex solution now such that

zp=Ceiωt


the constant C is determine by substituting the solution into the equation

D(zp)=(ω2+2iβω+ω20)Ceiωt=f0eiωt
C=f0(ω2+2iβω+ω20)

The amplitude of the solution is a complex number that may be cast in terms of a real amplitude times the complex exponential such that

C=Aeiδ

where the real amplitude A is given by

A2=CC=f0(ω2+2iβω+ω20)(f0(ω2+2iβω+ω20))
=f0(ω2+2iβω+ω20)(f0(ω22iβω+ω20))
=f20(ω20ω2)2+4β2ω2
C=Aeiδ=f20(ω20ω2)2+4β2ω2eiδ
zp=Ceiωt=f20(ω20ω2)2+4β2ω2eiδeiωt=Ceiωt=f0(ω20ω2)2+4β2ω2ei(ωtδ)


What is delta?

C=f0(ω2+2iβω+ω20)=Aeiδ
f0(ω2+2iβω+ω20)=Aeiδ
f0eiδ=A((ω20ω2)+2iβω)

Since f0 and A are not imaginary variables

The phase (δ) must be due to the remaining complex term ((ω20ω2)+2iβω)

To determine the angle δ we construct a right triangle in the complex plane where the leg along the real axis is given by (ω20ω2) and the other leg of the triangle is along the imaginary axis with a length of 2βω

tanδ=2βω(ω20ω2)
δ=tan1(2βω(ω20ω2))
The final complex solution si
zp=f0(ω20ω2)2+4β2ω2ei(ωtδ)


with

xp=Real|zp|=f0(ω20ω2)2+4β2ω2cos(ωtδ)

Complete Solution for the Driven Damped oscilaltor

x(t)=xh+xp=C1er1t+C2er2t+Acos(ωtδ)

where

r1=β+β2ω20
r2=β+β2+ω20
A=f0(ω20ω2)2+4β2ω2
δ=tan1(2βω(ω20ω2))


Forest_UCM_Osc#Damped_Oscillations_with_driving_source